Developmental origins of the human hypothalamic-pituitary-adrenal axis - Howland, Mariann A. (Expert Rev Endocrinol Metab, 2017)
INTRODUCTION: The developmental origins of disease or fetal programming model predicts that intrauterine exposures have life-long consequences for physical and psychological health. Prenatal programming of the fetal hypothalamic-pituitary-adrenal (HPA) axis is proposed as a primary mechanism by which early experiences are linked to later disease risk. AREAS COVERED: This review describes the development of the fetal HPA axis, which is determined by an intricately timed cascade of endocrine events during gestation and is regulated by an integrated maternal-placental-fetal steroidogenic unit. Mechanisms by which stress-induced elevations in hormones of maternal, fetal, or placental origin influence the structure and function of the emerging fetal HPA axis are discussed. Recent prospective studies documenting persisting associations between prenatal stress exposures and altered postnatal HPA axis function are summarized, with effects observed beginning in infancy into adulthood. EXPERT COMMENTARY: The results of these studies are synthesized, and potential moderating factors are discussed. Promising areas of further research highlighted include epigenetic mechanisms and interactions between pre and postnatal influences.